2021
DOI: 10.1101/2021.12.22.473889
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ureter single-cell and spatial mapping reveal cell types, architecture, and signaling networks

Abstract: Tissue engineering offers a promising treatment strategy for ureteral strictures, but its success requires an in-depth understanding of the architecture, cellular heterogeneity, and signaling pathways underlying tissue regeneration. Here we define and spatially map cell populations within the human ureter using single-cell RNA sequencing, spatial gene expression, and immunofluorescence approaches. We focused on the stromal and urothelial cell populations to enumerate distinct cell types composing the human ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…To differentiate the effects of our specific implementations of these algorithms from what is seen in practice, we performed TOWCAB analyses on a recent release of human urinary bladder cells (30,942 cells; 10 donors, aligned using Seurat’s MCCA), based on their released UMAP coordinates 38 . Indeed, we found that different cell-types were merged across batches including B- and urothelial-cells ( ED Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To differentiate the effects of our specific implementations of these algorithms from what is seen in practice, we performed TOWCAB analyses on a recent release of human urinary bladder cells (30,942 cells; 10 donors, aligned using Seurat’s MCCA), based on their released UMAP coordinates 38 . Indeed, we found that different cell-types were merged across batches including B- and urothelial-cells ( ED Fig.…”
Section: Resultsmentioning
confidence: 99%